Comparison of meat quality and glycolysis potential of two hybrid pigs in three-way hybrid model - Li, Yongxiang; He, Yang; Ran, Jinming; Huang, Ying; Li, Xian; Jiang, Hengxin; Li, Xueyan; Pan, Yangsu; Zhao, Sumei; Song, Chunlian; Pan, Hongbin; Hu, Hong (Frontiers in Veterinary Science, 2023)
To promote the development and utilization of Saba pigs and produce high-quality pork, the meat quality traits and glycolysis potential of Duroc × (Landrace × Yorkshire) (DLY), Berkshire × (Duroc × Saba) (BDS), and Duroc × (Berkshire × Saba) (DBS) three-way crossbred pigs were compared. Results showed that DLY had the highest live weight, carcass weight, lean meat percentage, drip loss, glycolysis potential, muscle diameter and the relative mRNA expression levels of type IIb muscle fibers, while the ultimate pH was the lowest (p < 0.05). The lightness value of DBS is the highest (p < 0.05). Among the three crossbred pigs, myristic acids, arachidic acids, palmitoleic acids and eicosenoic acids were the highest in BDS. These results indicated that the carcass traits of local crossbred pigs were worse than DLY pigs, but meat quality was markedly higher, with BDS showing the best meat quality.